Ovarian malignant melanoma metastasized from skin mimicking a benign cyst: a rare case report and mini-review of the literature - Ketenci Gencer, Fatma; Babaoğlu, Bülent; Usta Kurt, Zeynep Kübra; Yaşat Nacar, Hatice; Bektaş, Sibel (The European Research Journal, 2023)
Malignant melanomas, often appearing on the skin, rarely metastasize to internal organs and the ovaries are the least affected site. A 45-year-old female patient presenting with a skin lesion on the right side of the neck and diagnosed with malignant melanoma through excision biopsy also appeared to have lung metastasis and a nonspecific ovarian cystic mass of 6 cm after PET-CT scan was performed. Examination revealed a mass with the widest diameter of 9 cm and a surgical decision was made due to the rapid growth pattern. Tumor markers appeared to be within the normal range. Laparoscopic right salpingoopherectomy was performed and frozen section biopsy was obtained. The result was found to be malignant and complementary surgery was performed. Pathological examination of the cystic mass, which was detected to have only nonspecific findings on radiological exam, revealed tiny solid areas in its capsule. The patient was started on postoperative Dabrafenib + Trametinib treatment by oncology and was followed up without recurrence until the 24th postoperative month. At month 24, the brain metastasis with no response to radiotherapy occurred and the patient was lost on the 15th day after decompression surgery. It is important to send adnexal masses to the frozen even if they appear to have a benign character. In patients with a known history of primary cancer, the possibility of the metastasis from the primary tumor site to the ovary should be considered in those whose peroperative frozen section result is in favor of malignancy. Our case is the first case of ovarian malignant melanoma metastasis with a completely cystic and septa-free character in the literature.